1989
DOI: 10.1190/1.1442685
|View full text |Cite
|
Sign up to set email alerts
|

A calculus for finely layered anisotropic media

Abstract: Matrix algebra and group theory combine to offer a formalism for the simple calculation of the elastic, anisotropic, homogeneous medium which is equivalent, in the long‐wavelength limit, to a heterogeneous distribution of fine layers, each layer itself an elastic anisotropic medium. The properties of each anisotropic constituent in a set of fine layers map to an element of a commutative group. A reverse mapping returns the material properties of the constituent. Adding group elements gives the group element fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
0
5

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 363 publications
(137 citation statements)
references
References 6 publications
6
126
0
5
Order By: Relevance
“…Both approaches allow for different angular distributions of fractures. has shown that to first order the slip-interface model of Schoenberg and Muir (1989) is mathematically equivalent to that of . In other words, for any distribution of Schoenberg-Muir fractures, we can find some distribution of Hudson penny shaped cracks that gives the same anisotropic effective elastic medium, and vice versa.…”
Section: Fracture Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Both approaches allow for different angular distributions of fractures. has shown that to first order the slip-interface model of Schoenberg and Muir (1989) is mathematically equivalent to that of . In other words, for any distribution of Schoenberg-Muir fractures, we can find some distribution of Hudson penny shaped cracks that gives the same anisotropic effective elastic medium, and vice versa.…”
Section: Fracture Modelingmentioning
confidence: 99%
“…The second modeling approach, popularized by Schoenberg and Muir (1989), represents fractures as planes of discontinuous slip or very thin planar zones that are more compliant than the unfractured rock. The planes extend infinitely far.…”
Section: Elastic Theory Of Fracturesmentioning
confidence: 99%
“…Achieving this goal will require somewhat delicate analysis, and so we are careful not to attempt to push it beyond the realm where it is obviously still valid. To implement the quasi-static averaging method, we make use of the early work of Backus [3], as well as more recent work of Schoenberg and Muir [4]. (Also see Milton [22].)…”
Section: Motivation For This Approachmentioning
confidence: 99%
“…One goal of the present work is to develop such analytical methods. To accomplish these goals, generalizations of the Backus [3] and Schoenberg and Muir [4] approaches are used to analyze layered systems, whose layers are intrinsically anisotropic due to any physical and/or mechanical mechanism. The pertinent mechanism considered here is due entirely to locally aligned fractures.…”
Section: Introductionmentioning
confidence: 99%
“…The negative aspects of this approach (White 1983;Schoenberg and Muir 1989;Pyrak-Nolte et al 1990b;Zhao J et al 2006;Zhao XB et al 2006a, b) are due to the simplification of the discontinuous rock mass to an equivalent medium. This approach cannot work well in representing media where the fractures are relatively large and sparsely spaced (with spacing of the order of, or larger than, a seismic wavelength) (PyrakNolte et al 1990b).…”
Section: Introductionmentioning
confidence: 99%